2021
DOI: 10.1210/clinem/dgaa966
|View full text |Cite
|
Sign up to set email alerts
|

No Venous Thromboembolism Increase Among Transgender Female Patients Remaining on Estrogen for Gender-Affirming Surgery

Abstract: Background Both surgery and exogenous estrogen use are associated with increased risk of venous thromboembolism (VTE). However, it is not known whether estrogen hormone therapy (HT) exacerbates the surgery-associated risk among transgender and gender nonbinary (TGNB) individuals. The lack of published data has contributed to heterogeneity in perioperative protocols regarding estrogen HT administration for TGNB patients undergoing gender-affirming surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 16 publications
3
27
0
Order By: Relevance
“…This patient belonged to the cohort that had their hormone therapy suspended for 1 week prior to surgery. Of patients who continued hormone therapy, no VTE events were reported 50 . The VTE incidence rate in this study was comparable to the VTE incidence of 0% to 2% noted among patients undergoing similar surgeries 51 …”
Section: Misconceptions In Gender Affirming Caresupporting
confidence: 71%
“…This patient belonged to the cohort that had their hormone therapy suspended for 1 week prior to surgery. Of patients who continued hormone therapy, no VTE events were reported 50 . The VTE incidence rate in this study was comparable to the VTE incidence of 0% to 2% noted among patients undergoing similar surgeries 51 …”
Section: Misconceptions In Gender Affirming Caresupporting
confidence: 71%
“…811 papers were excluded as irrelevant, based on title and abstract reading. Hence, as shown in Figure 1, 99 studies were identified, of which 18 met the inclusion criteria (17,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). The studies by Asscheman and colleagues published in 1989 (50) and 2011 (51) were excluded since the population under investigation was already included in the paper by van Kesteren et al, 1997 (47).…”
Section: Study Selection and Quality Assessmentmentioning
confidence: 99%
“…Only 0.2% of trans men on testosterone ( n = 1893, median age = 26) developed thromboembolism in this study [88]. A retrospective study investigated the effect of estrogen (oral, transdermal, or intramuscular) therapy on the postoperative risk of developing VTE events in adult trans women ( n = 662), trans men ( n = 232), and nonbinary persons ( n = 25) [89]. Seventy‐one percent of trans women were taking spironolactone and 19% were on CPA in combination with estrogen therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Kozato et al. reported no increased risk of VTE when estrogen treatment was continued throughout surgery compared to suspended estrogen treatment [89]. No difference was detected in VTE rates among different routes of estradiol administration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation